Linking Southern Africa into South Africa's global value chains - Karishma Banga; Neil Balchin (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
This study explores the potential for South Africa to become an engine for intra- regional trade and industrial development by linking other Southern African countries to its global value chains and, in the process, improving its global trade competitiveness. The study identifies 'lead products' exported by South Africa, and then uses revealed comparative advantage and unit cost analysis to identify intermediate inputs in which Southern African countries have competitiveness to export that is currently untapped due to a lack of supply capacity or other factors. Such products are potential areas where regional investments could lead to the successful creation of regional value chains. The study also identifies 'new markets' for agricultural lead products exported by South Africa, which could open new opportunities for Southern Africa to supply intermediate agricultural inputs.
Keywords: F10; F15; 330; regional integration; regional value chains; Southern Africa; South Africa; global value chains